Positive Counsellor Characteristics with Sexual Minority Intimate Partner Violence Victims - Hancock, Ryan D. (Canadian Journal of Counselling and Psychotherapy, 2014)
Grounded theory procedures were combined with a queer theory perspective to examine what counsellor characteristics promote counsellor competency with sexual minority intimate partner violence victims (SMIPVVs). Ten counsellors participated in 2 rounds of individual interviews. Analysis of the textual data identified specific desirable counsellor traits that were identified to assist with developing counsellor competency. The author also discusses implications for counselling programs, supervision, and in-service seminars.